(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The scientific article explains in detail the important role of taxes in the state budget and its functions. Today, the main tasks of taxes are the role of taxes in the economic development of the country and its financial independence, as well as their contribution to the development of the country.